Synthesis and Antimicrobial Evaluation of 1-[4-{4-(2-Phenyl-4-oxo-3-quinazolinyl)phenyl}phenyl]-2-phenyl-4-aryl methane-5-oxo-imidazole - Undavia, N.K.; Trivedi, P.B.; Shanishchara, A.P.; Trivedi, Vasudev (Asian Journal of Chemistry, 2016)
Condensation of 4-{2-phenyl-4-oxo-3-quinazolinyl}-4'-amino diphenyl with 2-phenyl-4-aryl methane-5-oxazolones in the presence of pyridine afford 1-[4-{4-(2-phenyl-4-oxo-3-quinazolinyl)phenyl}phenyl]-2-phenyl-4-aryl methane-5-oxo-imidazole. All such compounds have shown moderate activity against Escherichia coli and Staphylococcus aureus.